2020
DOI: 10.21203/rs.3.rs-32987/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Personality Traits among Psychiatric Out-patients with Suicide Attempt Attending Tertiary Care Hospital in Eastern Nepal

Abstract: Background-Suicide attempt is a self-injurious behaviour with a nonfatal outcome. Studies report increasing hospital admissions due to self-inflicted harm (SIH) as well as a higher likelihood of associated psychosocial factors in SIH cases. We conducted a study to explore personality traits, socio-demographic profiles and psychiatric disorders among the suicide attempt cases in a tertiary care hospital setting of eastern Nepal.Methods-It was a descriptive study conducted with purposive sampling in a tertiary c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…Previous Nepalese studies report lack of education and poverty being associated with suicidal ideation (Garrison‐Desany et al., 2020 ; Hagaman et al., 2018 ) but current study showed the suicidality in 22% of well‐educated medical students from upper‐middle socioeconomic background. The possible causes of high prevalent suicidal ideation among medical students could be substance use, relationship issues, violence, and singlehood as found in eastern Nepal (Bhattachan et al., 2021 ). As our samples were biased for education, this finding needs further validation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous Nepalese studies report lack of education and poverty being associated with suicidal ideation (Garrison‐Desany et al., 2020 ; Hagaman et al., 2018 ) but current study showed the suicidality in 22% of well‐educated medical students from upper‐middle socioeconomic background. The possible causes of high prevalent suicidal ideation among medical students could be substance use, relationship issues, violence, and singlehood as found in eastern Nepal (Bhattachan et al., 2021 ). As our samples were biased for education, this finding needs further validation.…”
Section: Discussionmentioning
confidence: 99%
“…Attitudes toward suicide and literacy have been studied locally but with scales in English (Shah et al., 2022 ; Thapa et al., 2021 ). There are two scales, namely, literacy of suicide scale (LOSS) and Stigma of Suicide Scale (SOSS) that have been validated cross‐culturally in Australia, China, Turkey, Middle East, and Bangladesh (Al‐Shannaq & Aldalaykeh, 2021 ; Arafat et al., 2022 ; Batterham et al., 2013b , 2021 ; Calear et al., 2012 ; Chan et al., 2014 ; Han et al., 2017 ). Therefore, we aimed to adapt and psychometrically validate the LOSS‐short form (LOSS‐SF) and SOSS‐short form (SOSS‐SF) in Nepali and subsequently assess the level of stigma and literacy of suicide among the medical students of Nepal.…”
Section: Introductionmentioning
confidence: 99%